Schools' improvement capacity and responses to the COVID-19 pandemic: Evidence from schools serving disadvantaged communities - Beckmann, Laura; Koetter-Mathes, Stefanie; Klein, Esther Dominique; Bremm, Nina; Van Ackeren, Isabell (Frontiers in Education, 2022)
The goal of this paper is to analyze the relationship between six different dimensions of school improvement capacity (SIC) and schools' efforts to sustain teaching and learning as well as student well-being during the first lockdown in the context of the COVID-19 pandemic. Based on data from 13 qualitative interviews with principals and data from a standardized teacher survey at schools serving disadvantaged communities in North Rhine-Westphalia, Germany (N = 385 teachers), we assessed (1) the schools' level of SIC shortly before the lockdown, (2) their reported response to the lockdown with regard to sustaining student learning and well-being, and (3) similarities between the schools in terms of the combination of the level of SIC and the reported effort to address the challenges of distance learning. Our results suggest that two major groups of schools can be distinguished in terms of level of SIC. Furthermore, we identified a range of thematic clusters related to how schools acted during distance learning, each of which can be assigned to one or more dimensions of SIC. Finally, we identified four patterns, referring to different combinations of SIC and the schools' reported actions. The results indicate that schools with a higher initial SIC were more able to find flexible and pragmatic solutions in order to sustain student learning and well-being during distance learning. Our findings stress the importance of school improvement activities at schools serving disadvantaged communities in dealing with sudden challenges for teaching and learning, such as those encountered during COVID-19.
CRIS-Team WoS Importer:2022-12-23